Efficacy and safety of hetrombopag in the treatment of chemotherapy-related thrombocytopenia in solid tumors: a retrospective study - Yuan, Yuan; Tong, Qiang; Liu, Jia-hui; Kang, Ye (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the efficacy and safety of hetrombopag in the management of chemotherapy-induced thrombocytopenia (CIT) among patients with solid tumors, utilizing a retrospective cohort study design.MethodsThe study population comprised patients experiencing CIT due to chemotherapy for solid tumors, who received treatment at the General Hospital of Northern Theater Command from January 2023 to December 2024. Participants were categorized into four distinct cohorts based on their treatment regimens: the recombinant human thrombopoietin (rhTPO) monotherapy group, the hetrombopag monotherapy group, the combination therapy group (hetrombopag with rhTPO), and the recombinant human interleukin-11 (rhIL-11) monotherapy group. The primary outcomes evaluated included treatment response rate, alterations in platelet count (PLT), time to PLT recovery, differences in PLT counts pre- and post-treatment; secondary outcome measured encompassed rates of platelet transfusion, and incidence of adverse events (AEs).ResultsThe study included a total of 187 patients, distributed as follows: 64 in the rhTPO group, 37 in the hetrombopag group, 36 in the combination therapy group, and 50 in the rhIL-11 group. The hetrombopag + rhTPO group exhibited a significantly higher treatment response rate (P<0.05) compared to the other three groups. Furthermore, this group showed superior PLT levels on days 7 and 14, a greater increment in PLT post-treatment, and the shortest median time to PLT recovery to ≥100×109/L (P<0.05). Hetrombopag monotherapy demonstrated non-inferior PLT dynamics and treatment response rates compared to rhTPO/rhIL-11 (P>0.05). The four groups exhibited comparable PLT transfusion rates and a AEs incidence (P>0.05).ConclusionThe combination of hetrombopag and rhTPO therapy exhibits superior efficacy compared to monotherapy in the treatment of CIT in patients with solid tumors. This combination therapy is associated with rapid elevation of platelet counts and a shortened recovery period, while maintaining a favorable safety profile. Furthermore, hetrombopag monotherapy has shown efficacy comparable to that of rhTPO and recombinant human interleukin-11 (rhIL-11), thereby supporting its recommendation for clinical use.